Hypermethylation of N-Acetyltransferase 1 Is a Prognostic Biomarker in Colon Adenocarcinoma - Shi, Cheng; Xie, Li-ye; Tang, Yan-ping; Long, Long; Li, Ji-lin; Hu, Bang-li; Li, Ke-zhi (Frontiers in Genetics, 2019)
d normal tissues. The correlation between mRNA and methylation of NAT1 were analyzed. Survival analysis was performed on CpG sites at the promoter region of NAT1. Association of mRNA and CpG sites of NAT1 with clinicopathological features was analyzed. A independent GEO dataset was used to validate the results. Results: Expression of NAT1 mRNA was lower in COAD compared with normal tissues. The mean of eight CpG sites at the promoter region of NAT1 was higher in COAD compared with normal tissues. Five CpG sites were significantly negatively correlated to the NAT1 mRNA in COAD. Survival analysis showed that NAT1 mRNA and cg15797286, cg18509990 were associated with the overall survival (OS) of COAD patients. The jointed survival analysis revealed that combination of NAT1 mRNA with five CpG sites was significantly related to the OS of COAD patients. NAT1 mRNA and cg15797286 was associated with the T stage, N stage and clinical stage of COAD. Data from GSE128067 showed that cg15797286 was hypermethylation in colorectal adenomas with recurrence. Conclusions: Methylation of NAT1 is associated with the development of COAD, and may be a prognostic and treatment markers for COAD.